Remixe auf Hostingplattformen Eine urheberrechtliche Untersuchung filmischer Remixe zwischen grundrechtsrelevanten Schranken und Inhaltefiltern - Maier, Henrike (Internet und Gesellschaft, 2017)
Remixers recombine copyright-protected audiovisual material and distribute it via hosting platforms. To what extent does copyright law allow remixing and what is the impact of platforms' policies and filtering mechanisms for user uploads? Henrike Maier employs a comparative legal approach and focuses on the role of creative users' fundamental rights to investigate these questions.